2019
DOI: 10.3390/nano9030317
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Vanadium Oxide Nanoflakes for p-Type Ammonia Sensors at Room Temperature

Abstract: VO2(B), VO2(M), and V2O5 are the most famous compounds in the vanadium oxide family. Here, their gas-sensing properties were investigated and compared. VO2(B) nanoflakes were first self-assembled via a hydrothermal method, and then VO2(M) and V2O5 nanoflakes were obtained after a heat-phase transformation in nitrogen and air, respectively. Their microstructures were evaluated using X-ray diffraction and scanning and transmission electron microscopies, respectively. Gas sensing measurements indicated that VO2(M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 48 publications
2
13
0
Order By: Relevance
“…In accordance with the literature reports, water adsorption is possible on the surface of V 2 O 5 ; however, water dissociation does not take place on its surface, and hence, these two additional peaks are aroused because of the presence of doped Ru in V 2 O 5 . It can be noted from the results of the surface morphology analysis that it encouraged the formation of large, irregular, and rectangular flakes of micrometer and nanometer sizes on the catalyst surface (Figure c,d); perhaps it originated from the primary crystal grain platelets, which then self-assembled to form the flake-like structure . The additional mapping images revealed that no trace level impurities of any other elements were present, imparting that it was highly pure (Figure S5).…”
Section: Results and Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In accordance with the literature reports, water adsorption is possible on the surface of V 2 O 5 ; however, water dissociation does not take place on its surface, and hence, these two additional peaks are aroused because of the presence of doped Ru in V 2 O 5 . It can be noted from the results of the surface morphology analysis that it encouraged the formation of large, irregular, and rectangular flakes of micrometer and nanometer sizes on the catalyst surface (Figure c,d); perhaps it originated from the primary crystal grain platelets, which then self-assembled to form the flake-like structure . The additional mapping images revealed that no trace level impurities of any other elements were present, imparting that it was highly pure (Figure S5).…”
Section: Results and Discussionsupporting
confidence: 89%
“…55 It can be noted from the results of the surface morphology analysis that it encouraged the formation of large, irregular, and rectangular flakes of micrometer and nanometer sizes on the catalyst surface (Figure 6c,d); perhaps it originated from the primary crystal grain platelets, which then selfassembled to form the flake-like structure. 56 The additional mapping images revealed that no trace level impurities of any other elements were present, imparting that it was highly pure (Figure S5). Furthermore, the EDS analysis revealed the relative percentages of vanadium (61.0%), ruthenium (9.5%), and oxygen (29.5%) metal elements (Figure S6).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…These features enable V 2 O 5 to be utilized for numerous applications including gas sensing. Nanosized V 2 O 5 with different structures have been synthesized for the electrochemical sensing of ethanol [ 31 ], ammonia [ 32 ] and xylene [ 33 ]. However, the application of nanosized V 2 O 5 in the design of CTL-based sensors has seldom been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, it becomes important to develop gas sensors for real-time detection of NH 3 [4,5] as well as other gas pollutants in varied environments [6,7] . Chemiresistive sensors based on semiconductor metal oxides (e. g., ZnO [8][9][10] , V 2 O 5 [11] , TiO 2 [12] , SnO 2 [13] ) have been widely explored for this purpose, owing to their good selectivity, sensitivity and fast response towards ammonia detection. TiO 2 , a typical wide-band n-type semiconductor, exhibits appealing features for NH 3 sensing [14,15] , including low cost, nontoxicity, thermal and chemical stability, and suitable gassensing response.…”
Section: Introductionmentioning
confidence: 99%